2019
DOI: 10.1136/bmjopen-2019-034034
|View full text |Cite
|
Sign up to set email alerts
|

Does sex predict quality of life after acute coronary syndromes: an Australian, state-wide, multicentre prospective cohort study

Abstract: ObjectiveWomen have reported higher mortality and major adverse cardiovascular events (MACE) following acute coronary syndromes (ACSs) compared with men. With this in mind, we aimed to identify predictors of poor quality of life (QoL) post-ACS as our primary outcome. We examined predictors of MACE, major cerebrovascular events and major bleeding as our secondary outcome.DesignProspective cohort study.Setting30 metropolitan centres across the Victorian Cardiac Outcomes Registry network.Participants16 517 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Following hospital discharge, further sex and gender discrepancies become evident. One notable example is that women are less likely to be referred to, or participate in a cardiac rehabilitation program than men [45,73,74]. despite its proven efficacy in reducing cardiac mortality for both sexes.…”
Section: Management and Post MI Carementioning
confidence: 99%
See 1 more Smart Citation
“…Following hospital discharge, further sex and gender discrepancies become evident. One notable example is that women are less likely to be referred to, or participate in a cardiac rehabilitation program than men [45,73,74]. despite its proven efficacy in reducing cardiac mortality for both sexes.…”
Section: Management and Post MI Carementioning
confidence: 99%
“…Female sex has been shown to be independently associated with reduced quality of life after a MI, including increased pain, anxiety and depression [74]. This is likely influenced by personality traits and social roles that are traditionally ascribed to women, or more specifically, to the female gender.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…Literature also support these findings that QOL is better in males than females who underwent same PCI procedure. [16][17][18] Uchmanowicz et al also found that female patients scored lesser than males in all domains of SF-36. 19 It may be due to the fact that females are at greater risk recurrent angina post PCI as compared to males.…”
Section: Discussionmentioning
confidence: 92%
“…An analysis of 16,517 ACS patients (22.9% women) who were treated with PCI demonstrated that female sex was independently associated with significantly poorer mobility, more issues with personal care, and greater symptoms of anxiety and depression at 30 days, despite no sex difference in rates of bleeding, stroke, or MACE. 168 Similarly, a single center study of 1072 patients (27.5% women) who underwent CABG demonstrated that women reported experiencing only about 50% of the physical functional improvement at 6 months compared with men. 169 These findings have been shown to be consistent in the younger population as well.…”
Section: Health Status Outcomes In Women After Revascularizationmentioning
confidence: 98%